2017
DOI: 10.1111/ajt.13957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mixed Xenogeneic Porcine Hematopoietic Chimerism on Human NK Cell Recognition in a Humanized Mouse Model

Abstract: Mixed chimerism is a promising approach to inducing allograft and xenograft tolerance. Mixed allogeneic and xenogeneic chimerism in mouse models induced specific tolerance and global hyporesponsiveness, respectively, of host mouse NK cells. In this study, we investigated whether pig/human mixed chimerism could tolerize human NK cells in a humanized mouse model. Our results showed no impact of induced human NK cell reconstitution on porcine chimerism. NK cells from most pig/human mixed chimeric mice showed eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…In such animals, we observed that, while human NK cells developing in non‐chimeric mice were able to kill and produce cytokines in response to porcine lymphoblasts, those developing in mixed xenogeneic chimeras lacked cytolytic activity against porcine lymphoblasts. In some such animals, the lack of pig‐specific killing was associated with a failure to kill the human class I MHC‐deficient target K562 (ie, global hyporesponsiveness), whereas in others the tolerance was donor‐specific and associated with significant ability to lyse K562 targets . These results are consistent with the observation that many human killer inhibitory receptors (KIRs) do not interact with porcine MHC molecules, whereas a few receptors do .…”
Section: Lessons From Mixed Chimerism Induction In Rodent and Humanizsupporting
confidence: 75%
See 1 more Smart Citation
“…In such animals, we observed that, while human NK cells developing in non‐chimeric mice were able to kill and produce cytokines in response to porcine lymphoblasts, those developing in mixed xenogeneic chimeras lacked cytolytic activity against porcine lymphoblasts. In some such animals, the lack of pig‐specific killing was associated with a failure to kill the human class I MHC‐deficient target K562 (ie, global hyporesponsiveness), whereas in others the tolerance was donor‐specific and associated with significant ability to lyse K562 targets . These results are consistent with the observation that many human killer inhibitory receptors (KIRs) do not interact with porcine MHC molecules, whereas a few receptors do .…”
Section: Lessons From Mixed Chimerism Induction In Rodent and Humanizsupporting
confidence: 75%
“…Importantly, recent studies in the pig‐to‐humanized mouse (H. W. Li and M. Sykes, unpublished data) and pig‐to‐baboon model (H. Watanabe, T. Tanabe, K. Yamada, unpublished data) are consistent with the prediction that mixed chimerism can tolerize anti‐pig xenoantibodies, suggesting that the immmunobiology of Nab production and tolerization will be translatable from the rat→mouse model to the large animal and human transplant settings.…”
Section: Lessons From Mixed Chimerism Induction In Rodent and Humanizsupporting
confidence: 65%
“…Appropriate TCR expression and in vitro MART1 TCR responses were assessed using stably transfected JRT3‐T3.5 cells, a variant Jurkat cell line that does not express TCRβ . Cells were cultured in complete RPMI 1640 medium (Thermo Fisher Scientific) supplemented with 10% heat‐inactivated fetal bovine serum (Gemini Bio‐Products), 10 mmol/L HEPES buffer (Gibco), 20 mmol/L l ‐glutamine (ACROS Organics), 1 mmol/L sodium pyruvate (Fisher BioReagents), and 0.2% 2‐Mercaptoethanol (MP Biomedicals, LLC).…”
Section: Methodsmentioning
confidence: 99%
“…Mixed chimerism also has the capacity to tolerize natural killer (NK) cells (54). In the case of allogeneic chimerism, the tolerance is specific for the donor, with otherwise preserved NK cell function.…”
Section: Tolerance-inducing Strategies Across Xenogeneic Immunolomentioning
confidence: 99%
“…However, in the rat-to-mouse xenogeneic chimerism model, mouse NK cells were rendered globally unresponsive by the presence of even low levels of rat chimerism (55). In the pig-human mixed chimerism model in humanized mice, we recently showed that human NK cells are rendered tolerant by porcine mixed chimerism, as reflected in some cases by specific unresponsiveness with otherwise preserved NK cell function and, in others, global hyporesponsiveness (54). Collectively, our data argue for a mechanism of NK cell tolerance involving anergy induced by repeated, unopposed activating signals, as opposed to a requirement for licensing by the presence of inhibitory ligands, as we have discussed previously (56).…”
Section: Tolerance-inducing Strategies Across Xenogeneic Immunolomentioning
confidence: 99%